Transformational Leadership and Work Competence: A Path to Enhanced Employee Performance - Rahayu Noviany Kuswandi; Asep Jamaludin; Nandang Nandang (Lembaga Riset dan Inovasi Al-Matani, 2025)
The aim of this research is to analyze the influence of transformational leadership style and work competency on employee performance. The research method used is quantitative research with associative research type. The population in this study were all employees of the PPIC Dept. PT XYZ with a total research sample of 70 employees. The sampling technique uses saturated samples and uses collection techniques with observation instruments, questionnaires and interviews. Then the data was analyzed using multiple linear regression analysis using SPSS version 29 software. The results of the research partially showed that transformational leadership style had no significant influence on employee performance and work competency had a significant influence on employee performance. The research results simultaneously show that transformational leadership style and work competency have a significant effect on employee performance. The implication of this research is that it is necessary to improve employee performance, develop programs, train and improve leadership systems.